The positional demands of explosive actions in elite soccer: Comparison of English Premier League and French Ligue 1 - Ryland Morgans; Wonwoo Ju; John Radnor; Piotr Zmijewski; Ben Ryan; Chris Haslam; Matthew King; Ronan Kavanagh; Rafael Oliveira (Biology of Sport)
The aims of the present study were to: (i) quantify accelerations and decelerations of soccer players during match-play across two consecutive seasons from the English Premier League (EPL) and Ligue 1 (L1); and (ii) compare any positional differences between the two leagues. Fifty-eight male professional soccer players were monitored during all league matches ( n = 144) across seasons 2020/21 and 2021/22. The absolute number of accelerations (> +3 m/s −2 ) and decelerations (< -3 m/s −2 ) and accelerations and decelerations per minute were examined. The relative number of accelerations and decelerations across all positions was higher with moderate effect sizes in the EPL when compared to L1 ( p < 0.001, for both). Significant differences were observed in accelerations and decelerations across all playing positions ( p < 0.001 and p = 0.001 respectively, with moderate to very large effect sizes), except for centre forwards (CF) (accelerations p = 0.40; ES = 0.16; decelerations p = 0.97; ES = 0.01). This study provides valuable insights into the positional acceleration and deceleration differences in the EPL and L1, which should be considered in match running performance evaluations. While confirming higher accelerations and decelerations in the EPL, the unique case of CF challenges current evidence, emphasising the need for a more granular understanding of the positional demands of explosive actions incorporating accelerations and decelerations in elite soccer.